1.
a1=-1
r=3
n=51
Korzystamy z wzoru:
an=a1+(n-1)r
a51=a1+50r
a51=-1+50·3
a51=149
S51=[(a1+a51)/2]·51
S51=(-1+149)/2·51
S51=3774
Odp. C
2.
a)
15+11+7+...+(-37)
a1=15
r=11-15=-4
an=-37
an=a1+(n-1)r
-37=15+(-4)·(n-1)
-37=15-4n+4
4n=19+37
4n=56|:4
n=14
S14=[(a1+a14)/2]·14
S14=(a1+a14)·7
S14=(15+(-37))·14
S14=-308
b)
1/6+1/3+1/2+...+5/3
a1=1/6
r=1/3-1/6
r=1/6
5/3=1/6+1/6(n-1)
5/3=1/6+1/6n-1/6
1/6n=5/3 |·6
n=10
S10=[(a1+a10)/2]·10
S10=(1a+a10)·5
S10=(1/6+5/3)·5
S10=11/6·5
S10=55/6
3/
a)
3,5+3,7+3,9+...+a20
a1=3,5
r=3,7-3,5
r=0,2
a20=a1+19r
a20=3,5+0,2·19
a20=3,5+3,8
a20=7,3
S20=[(a1+a20)/2]·20
S20=(a1+a20)·10
S20=(3,5+7,3)·10
S20=108
b)
2-1-4-...+b15
b1=2
r=-1-2
r=-3
b15=b1+14r
b15=2+(-3)·14
b15=2-42
b15=-40
S15=[(b1+b15)/2]·15
S15=[(2+(-40))/2]·15
S15=-19·15
S15=-235